2023
DOI: 10.1001/jamaneurol.2022.4156
|View full text |Cite
|
Sign up to set email alerts
|

Time to Change the Current Clinical Classification of Multiple Sclerosis?

Abstract: to date. Much of this strength is due to the breadth of studies included, assessment of bias, and depth of statistical analysis of outcomes and potential confounders. While we await results from RCTs such as the ongoing Aging and Cognitive Health Evaluation in Elders (ACHIEVE; NCT03243422) trial and the upcoming Early Age-Related Hearing Loss Investigation (EARHLI) trial, this meta-analysis provides substantial reason to pursue further study of the relationship between hearing loss and cognitive decline/dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Only after a certain time and continuous accumulation of damage, the brain reserve may not be able to cope with the structural injury, explaining the correlation of PIRA with higher age and/or longer disease duration . Still, PIRA may remain undetected due to the low granularity of our clinical measures, highlighting the importance of standardized, quantitated and structured assessment of patients with MS with sensitive and specific measures, allowing for more precise correlation studies with markers of progression and better targeted therapeutic interventions …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only after a certain time and continuous accumulation of damage, the brain reserve may not be able to cope with the structural injury, explaining the correlation of PIRA with higher age and/or longer disease duration . Still, PIRA may remain undetected due to the low granularity of our clinical measures, highlighting the importance of standardized, quantitated and structured assessment of patients with MS with sensitive and specific measures, allowing for more precise correlation studies with markers of progression and better targeted therapeutic interventions …”
Section: Discussionmentioning
confidence: 99%
“…33 Importantly, most studies confirmed that PIRA accounted for a higher proportion of confirmed disability accruals in patients re-ceiving DMT compared with those without or undergoing placebo treatment. 7,13,16,18,25,43 Discussion Observational and controlled clinical trials provide unequivocal evidence that PIRA is the most frequent manifestation of disability accumulation across the full spectrum of traditional MS phenotypes, including CIS and early RRMS, thus challenging the conceptual distinction between relapsing and progressive disease courses or stages. The reported proportion of patients experiencing PIRA varies depending on (1) the definition used (EDSS vs composite measures, fixed vs roving baseline), ( 2) population under study (randomized clinical trials vs observational data, CIS/early RRMS vs late RRMS vs progressive MS), and (3) length of follow-up (eTable 3 in the Supplement).…”
Section: Treatment Of Piramentioning
confidence: 99%
See 3 more Smart Citations